LIFESTYLE MODIFICATION OF OFFICIAL WORKERS W.S.R. TO CORPORATE WORKERS (International Journal of Ayurveda and Pharma Research, 2019)
The people working in big private companies may be considered as corporate workers. Due to changed lifestyle of the official workers, they commonly face psychological stress. This stress is mainly caused by the internal pressure to achieve success in goals. Stress may be considered as a major reason in lowering the body’s own resistance power and as a result may develop physical and mental ailments. Majority of official workers are prone to lifestyle disorders due to poor eating habits, load of work, physical inactivity and wrong body postures. Ayurveda can do very much in this field. In Ayurveda, where stress is known as Sahasa, Acharya Charak has advised to avoid Sahasa as it adversely affects the body. In Ayurveda ancient Acharyas has mentioned some Ayurvedic preparations and daily lifestyle regimen which can be helpful in lifestyle modification of corporate workers. Among these, Abhyanga, yoga exercises and Pranayam play a very important role. Therapeutically, Nasya Karma, and Shirodhara are helpful in reducing the symptoms of lifestyle disorders. Some Ayurvedic preparations has been described by the ancient Acharyas like Shankhapushpi, Bramhi, Jatamansi, Sarasawatarishta, Ashwagandha. This article is an attempt to analyze the lifestyle modifications for corporate workers with the help of Ayurveda, meditation, yoga, physical exercises and balanced diet together play an important role in rejuvenating the health of an individual on physical, mental and emotional level with a combination of benefits like Panchkarma therapy, herbal medicines, good Dinacharya and nutritious diet.